Cooperação regulatória em saúde: uma visão latino-americana - Alegre, Mariana de Angelo Silva (2020)
Health is acknowledged as a human right, only reaching this status once the consequences of its violation were realized, in the control of epidemics that interfered in international trade, war crimes and the launching of products without scientific evidence of its safety, quality and efficacy. The thalidomide tragedy has transformed the regulatory health view globally. In Brazil, the Constitution determines that health is a fundamental right and a duty of the State, and its universal character is admitted. When establishing the sanitary surveillance system, within the competence of the Unified Health System, the State was responsible for the market regulation, also constitutionally foreseen, with an intrinsic character of sanitary risk. Unjustified regulatory barriers are also characterized by difficult access to health, which must be solved. Globally, sanitary and phytosanitary barriers are an important factor in the non-facilitation of trade. In order to soften the different approaches among various health authorities, several international bodies have begun working on regulatory cooperation guidelines, such as harmonization, mutual recognition, regulatory convergence and reliance, following the principles of good regulatory practices. Thus, considering that regulatory cooperation is fundamental for economic integration, are national health regulatory agencies in Latin America using the mechanisms of regulatory harmonization and convergence in line with international economic agreements? How far has Latin America advanced in terms of regional integration in the circulation of goods of interest to health? What international procedures could be adopted by Latin American regulators to ensure economic integration? Thus, the objective of this study is to evaluate the representativeness and effectiveness of regulatory cooperation mechanisms for the commercialization of products of interest to health in Latin America. The methodology employed is the systematic and historical-comparative analysis of cooperation in Regulatory Health Law in Latin America, using analysis, synthesis, deduction, induction, comparative method and systematic interpretation of legal norms. The research is justified in the core of International Economic Relations Law by addressing how international Regulatory Health Law, through the tool of regulatory cooperation, is crucial to achieving economic integration through the transit of food products, cosmetics, medical devices and drugs, in addition to improving access to health as a fundamental right